2016
DOI: 10.1177/0890117116639559
|View full text |Cite
|
Sign up to set email alerts
|

Our Health Is in Our Hands

Abstract: A multifaceted SMC that coincides with prevention programs can effectively raise attention to health issues and activities in a high-risk population at a relatively low cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…In recent years, many studies found that some plant extract or pure compounds could reduce body weight and improve NAFLD [1,8,31,32]. Rutin could improve NAFLD by suppressing hepatic lipid levels and oxidative injury in mice [33], and curcumin could ameliorate the progression of NASH and liver damage and in HFD mice by regulating the HMGB1-NF-κB pathway [34].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies found that some plant extract or pure compounds could reduce body weight and improve NAFLD [1,8,31,32]. Rutin could improve NAFLD by suppressing hepatic lipid levels and oxidative injury in mice [33], and curcumin could ameliorate the progression of NASH and liver damage and in HFD mice by regulating the HMGB1-NF-κB pathway [34].…”
Section: Discussionmentioning
confidence: 99%
“…Such interventions should be initiated early in pregnancy and continue throughout the pregnancy, as major short-and long-term health consequences for both the mother and the child are likely. • Develop and implement national diabetes plans as well as regional strategies promoting local partnerships with communities and stakeholders [38] • Governments should support the implementation of interdisciplinary care teams, with special regard to the involvement of pharmacists [39] • Improve the transparency of product ingredients using mandatory simple and intuitive nutrition or menu labelling [40] • Set up government food benefit programmes to incentivise the purchase of fruit and vegetables [41] • Support the certification of digital devices and apps to improve access to evidencebased health information [42] • Use narrative and visual messages to improve diabetes awareness [43] • Support interpretative nutrition labelling, like traffic lights, to decrease SSB sales [41] • Strengthen the framing of diabetes as a problem to be tackled on the societal level [44] • Raise taxes on unhealthy products (and consider the liability for adverse health effects of food and beverage products) and reinvest the money in local infrastructure (outdoor gyms and playgrounds) [45] Pregnant women and young families • Screen high-risk groups (elevated risk due to family history, increased BMI) for early detection of GDM [46] as a precondition for lifestyle change • Give advice regarding healthy eating and set activity targets during pregnancy [47,48] • Give advice regarding the benefits of breastfeeding [49] • Employ multimedia communication strategies to increase the widespread knowledge of diabetes risk during pregnancy [50,51] Children and adolescents…”
Section: Pregnant Women and Young Familiesmentioning
confidence: 99%
“…To enhance diabetes awareness both in the general population and in at-risk groups (e.g. individuals with impaired glucose tolerance or those with low literacy), governments should employ communication strategies based on targeting, the use of multiple media channels [42] and the involvement of an individual's support network, such as family and friends, as well as physicians [92][93][94][95]. Government strategies aiming to decrease the prevalence of risk factors for GDM should employ a broad spectrum of media channels to increase awareness rather than relying solely on the effectiveness of prepregnancy care [50,51].…”
Section: Evidence-based Communication Strategiesmentioning
confidence: 99%
“…Similar to our findings, The Food Hero study - a social media campaign targeted at SNAP-eligible families with children - found increased positive beliefs about FV among participants. (50) Although previous studies have tested social media approaches for behavioral interventions (51; 52; 53; 54) , to our knowledge, BHCK was the first study to combine these strategies into a multilevel multicomponent community-based nutrition intervention. The use of social media to provide a platform for actionable information and social support for families with children has been recommended in the obesity prevention literature (54; 55; 56) and is being further tested in ongoing community-based trials.…”
Section: Discussionmentioning
confidence: 99%